2005
DOI: 10.1093/rheumatology/kei203
|View full text |Cite
|
Sign up to set email alerts
|

Anti-CCP antibodies measured at disease onset help identify seronegative rheumatoid arthritis and predict radiological and functional outcome

Abstract: This study confirms the diagnostic utility of anti-CCP(2) antibodies in early RA, particularly in seronegative patients, in whom anti-CCP(2) positivity also conferred prognostic utility for radiographic and functional outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
78
3
4

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(93 citation statements)
references
References 18 publications
8
78
3
4
Order By: Relevance
“…Previous studies have reported anti-CCP antibody positivities in about 34-60% of RFnegative RA patients (Lee and Schur 2003;Quinn et al 2005). Anti-CCP antibodies were positive in 26.3% of RF-negative RA patients in our study.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Previous studies have reported anti-CCP antibody positivities in about 34-60% of RFnegative RA patients (Lee and Schur 2003;Quinn et al 2005). Anti-CCP antibodies were positive in 26.3% of RF-negative RA patients in our study.…”
Section: Discussionsupporting
confidence: 56%
“…However, although RF has little diagnostic utility, its place has been retained in practice because of its prognostic ability and the lack of alternative tests (Quinn et al 2005). It is known as a nonspecifi c marker, since it may also be detected in patients with other autoimmune and infectious diseases and even in healthy persons.…”
Section: Participants and Methodsmentioning
confidence: 99%
“…T he production of autoantibodies against citrullinated protein Ags (ACPA) is a unique marker for rheumatoid arthritis (RA) (1)(2)(3)(4)(5)(6). These Abs are present in the majority of RA patients, are virtually never observed in healthy people, and are only rarely found in persons with other conditions (7).…”
mentioning
confidence: 99%
“…21,22 According to some authors, CCP2 seems to be as sensitive as RF IgM and more specifi c. Its advantage is to detect antibodies in approximately 15% of RA patients who are negative for RF. [23][24][25][26][27][28][29][30][31] However, Nishimura et al, 8 in their meta-analysis about anti-CCP and RF accuracy for RA, have concluded that isolated positivity for anti-CCP is more specifi c than isolated positivity for RF IgM in the RA diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in isolation, CCP2, CCP3 and CCP3.1 showed, in our study, anti-CCP prevalence below that of RF IgM and similar to that of RF IgA, which differs from many studies previously reported. [23][24][25][26][27][28][29][30][31] The sensitivity, specifi city and cost-benefi t difference between the three techniques to detect anti-CCP is still a controversial subject in the literature, requiring further studies in different populations. 32 In 2005, a third generation of anti-CCP (CCP3) was made available for RA laboratory diagnosis.…”
Section: Discussionmentioning
confidence: 99%